Spore morphology and sporoderm ultrastructure in Adiantopsis Fée (Pteridaceae-Pteridophyta) from Argentina - Piñeiro, Maria Raquel (2006)
The aim of this study is to analyse, describe and compare the spores of the two Adiantopsis species that grow in Argentina, A. chlorophylla (Sw.) Fée and A. radiata (L.) Fée. The study used herbarium material observed with light microscopy (LM), scanning electron microscopes (SEM) and transmission electron microscopes (TEM). The spores of both species are trilete with an echinate surface. The exospore is smooth, two-layered in section; both layers with different thickness and contrast. Depending on the plane of sectioning, channels are seen running through the exospore and in the apertural region. The perispore strongly contrasted when seen with TEM, is two-layered and bears ornamentation. The two layers have different thickness and structure. The inner layer P1 is the thickest layer and has three strata, which form the sculptural elements. The outer layer P2 covers all the surfaces of P1. Two levels of ornamentation are clearly distinguished: a basal level composed of fused ridges, and an upper level composed of echinae. The spores of A. chlorophylla are triangular-globose in polar view, with convex sides, 25 - 50 μm in equatorial diameter and have more ornamental processes per surface unit than the spores of A. radiata. The spores of A. radiata are triangular in polar view and 30 - 40 μm in equatorial diameter. Size and ornamentation help to establish differences at species level, and together with the exomorphological characteristics of the sporophyte, contribute to the systematics of this genus.